Wojewódzki Zjazd Spółdzielczy. (Gdańsk : [s.n.], 1947)
Afisz z programem zjazdu, który miał miejsce w Gdańsku i Gdyni 15.12.1947 r.
Keywords: Spółdzielnie -- Polska -- Gdańsk -- 1945-1970 -- druki ulotne; Spółdzielnie -- Polska -- Gdańsk -- 1945-1970 -- źródła; Spółdzielnie -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- źródła